Fiber optic displacement sensor for imaging of tooth surface roughness - Rahman, H.A.; Rahim, H.R.A.; Ahmad, Harith; Yasin, M.; Apsari, R.; Harun, Sulaiman Wadi (Elsevier, 2013)
A simple and inexpensive method using fiber optic displacement sensor is proposed for measurements of tooth surface roughness based on the intensity modulation technique. A light beam was launched onto a tooth surface via a bundled fiber. The reflected light from the surface was collected and measured as a function of lateral distance to estimate the roughness of the surface. The system’s roughness measurement capability was successfully tested on teeth surfaces of varying surface texture. In the measurement, the average surface roughness, Ra for the canine, molar, hybrid composite resin and artificial teeth surfaces were estimated to be approximately 121, 62.6, 39 and 37.6 μm, respectively. The experimental results indicated the capability of implementation of the displacement sensor for the imaging of the tooth surface profile as well as a micron-size roughness estimator with a measurement error of less than 2.35%.